Peran Guru Dalam Meningkatkan Minat Dan Kemampuan Membaca Al-Quran Siswa Kelas II SDN Paccinogan Unggulan Kabupaten Gowa - Sri Ramadani; Syarifuddin Cn Sida; Ainun Jariah (PT PUSTAKA CENDEKIA GROUP, 2024)
The aim of this research is to review and determine the abilities and roles of teachers in reading the Koran for class III students at SDN Pancinongan Unggulan. This research is descriptive qualitative, which aims to describe and discover symptoms or phenomena in detail and in depth without using measurements. The method applied in this research is a descriptive method, which aims to describe a symptom or event systematically and accurately in a particular area. Data collection techniques used include observation, interviews and documentation. The data in this research can be divided into two types, namely primary data sources and secondary data sources. The data analysis technique applied in this research is qualitative data analysis using the Miles and Huberman model data analysis technique. The technical stages of the analysis are data reduction, data display and construction or verification. This research resulted in interest in reading the Al-Qur'an for class III students at Paccinongan Unggulan State Elementary School, namely that at Pacciongan Unggulan Elementary School, there was still a majority of class III students who still lacked the will, due to the lack of improvement and quality of Al-Quran teachers and lack of motivation. and encouragement from parents in increasing interest in reading the Al-Quran and the role of teachers in increasing interest and ability to read the Al-Quran involves the process of educating, guiding and nurturing students.